Understanding Digital Consumer Behaviour: Consumer Trust Mediating e-WOM Credibility, Responsiveness, Decisions, and Satisfaction - Ahmad Sopyan; Teguh Maianto; Marthaleina Ruminda; Kamsariaty Kamsariaty; Purbanuara Parlindungan (Goodwood, 2026)
Purpose: This study examines the effects of e-WOM credibility and digital responsiveness on transaction decisions and customer satisfaction, with consumer trust as a mediating mechanism in e-commerce.Research Methodology: A quantitative, explanatory, cross-sectional survey was conducted using purposive sampling of 210 e-commerce users. Data were collected through a five-point Likert questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.Results: Consumer trust significantly influences customer satisfaction (β = 0.462) and transaction decisions (β = 0.418). E-WOM credibility significantly affects consumer trust (β = 0.466) and transaction decisions (β = 0.257), but not customer satisfaction directly. Digital responsiveness significantly improves customer satisfaction (β = 0.386), but does not significantly affect trust or transaction decisions. Consumer trust significantly mediates the effects of e-WOM credibility on customer satisfaction (β = 0.215) and transaction decisions (β = 0.195).Conclusion: Trust is a central mechanism in digital consumer behavior, while responsiveness primarily functions as a satisfaction-enhancing factor.Limitation: The cross-sectional design, self-reported data, selected variables, and limited generalizability constrain the findings.Contribution: The study extends the S–O–R perspective by demonstrating distinct pathways through which informational and service-related stimuli influence e-commerce outcomes.